DEVELOPMENT OF INSTRUCTIONAL COMPUTER MODEL FOR DESIGNING E-LEARNING MODULES FOR HEARING IMPAIRED PERSONS (TECHNICAL APPROACH) - Hussein, Karim Q; Jabbar, Qabas Abdal Zahraa (International Journal of Research -GRANTHAALAYAH, 2019)
To develop an e-learning module for a certain topic, many factors must be taken into account. Each factor deals with a specific area of study, therefore such development does not represent a task of software skills, programming, or developing of multimedia. But it is an integrated work in which software development represents the main tool and the main factor of that work. For Hearing Impaired Persons (HI) this work would be more difficult because the designer must consider specific factors represent the environment of teaching / learning process for HI person via e-Learning. According to our survey we did not find such systematic integrated model which would be a typical guide for developing e-learning modules (eLMs) for HI persons so that the developed eLMs would be systematic and realizing effective instructional outcomes. The integrated and systematic approach, which has been used during the development of this model, results in a model that processes all requirements of designers who would like to develop their own eLMs for any topic and for any category of HI persons.